Characterization of Ag:Zno Thin Films and Their Use in Photoelectrocatalytic Degradation Of Methylene Blue (Mb) - Karki, Bhishma; Nakarmi, Jeevan Jyoti; Singh, Rhiddi Bir; Banerjee, Manish (Journal of Institute of Science and Technology, 2018)
The synthesis of functional nano-particles via spray pyrolysis technique (SPT), especially those of catalytic nature, has attracted the interests of scientists and engineers, as well as industries. The rapid and high temperature continuous synthesis yields nano-particles with intrinsic features of active catalysts, that is, high surface area and surface energetic. For these reasons, SPT finds applications in various thermally inducible catalytic reactions. However, the design and synthesis of photocatalysts by SPT requires a knowledge set which is different from that established for thermal catalysts. Unknown to many, this has resulted in frustrations to those entering the field unprepared, especially since SPT appears to be an elegant tool in synthesizing oxide nano-particles of any elemental construct. From simple oxide to doped-oxide, and mixed metal oxide to the in situ deposition of noble metals, this Perspective gives an overview on the development of photocatalysts made by SPT in the last decade that led to a better understanding of the design criteria. Various challenges and opportunities are also highlighted; especially those beyond simple metal oxides, which perhaps contain the greatest potential for the exploitation of photocatalysts design by SPT. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 109-116